Limosilactobacillus reuteri DSM 17938 and ATCC PTA 6475 for the treatment of moderate to severe irritable bowel syndrome in adults: a randomized controlled trial - Cruchet, Silvia; Hirsch, Sandra; Villa-López, Diana; Moreno-Portillo, Mucio; Palomo, Juan C.; Abreu-Abreu, Ana T.; Abdo-Francis, Juan M.; Jiménez-Gutiérrez, Carlos; Rojano, Martin; López-Velázquez, Gabriel; Gutiérrez-Castrellón, Pedro (Frontiers in Gastroenterology, 2024)
Background Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder in adults. Systematic reviews with meta-analyses have demonstrated the efficacy and safety of probiotics in improving symptoms of IBS. Aim The aim of the study was to demonstrate the efficacy and safety of Limosilactobacillus reuteri (L. reuteri) DSM 17938 combined with L. reuteri ATCC PTA 6475 regarding improving the symptoms associated with IBS in adults. Methods A randomized, double-blind, placebo-controlled clinical trial was conducted in 140 adults aged 18 years to 65 years with a diagnosis of IBS (based on the Rome IV criteria). After 2 weeks of washout, subjects were randomized to receive either 2 × 108 colony-forming units (CFUs) of L. reuteri DSM 17938 combined with L. reuteri ATCC PTA 6475 plus standard of care or placebo plus standard of care for 14 weeks, followed by a post-intervention period of 2 additional weeks. Changes in gastrointestinal symptoms (as measured with the GSRS-IBS), stool pattern (as measured with the Bristol scale), quality of life, depression and anxiety, frequency of adverse events, and fecal calprotectin concentrations were evaluated. Results In total, 70 subjects were allocated to receive L. reuteri and 70 were allocated to receive placebo. During the pre-randomization phase, no differences were observed between the groups in terms of IBS-associated symptoms and stool consistency. Starting at week 6 of the intervention, subjects in group L. reuteri showed a significant improvement in IBS-associated symptoms (p < 0.01). A significant improvement was also observed in fecal calprotectin concentration in the L. reuteri group at the end of interventions (30.2 ± 11.8 mg/g of stool in the L. reuteri group and 41.6 mg/g ± 10.7 mg/g in the placebo group; p = 0.019). The frequency of adverse events was similar between groups. Conclusions A twice-a-day intervention for 14 weeks is safe and effective, reduces the symptoms associated with IBS in adults aged 18 years to 65 years, improves stool consistency, and reduces symptoms associated with anxiety after 6 weeks.